Cointegration analysis of social services expenditure and human capital development in Malaysia: A bound testing approach - Sapuan N.M.; Sanusi N.A. (2023)
Government expenditure on social services is essential to the development of the economy. This fact also applies to Malaysia, a developing country that aspires to become a developed nation in a few years to come. As the Malaysian government plays a dominant role in financing public education and health services, an analysis on its investment in these areas, if made available, would be able to assist policymakers in generating a strategic plan to enhance human capital development and economic growth. Hence, the aim of this study is to investigate the long-run and short-run relationships between economic growth and social services expenditure with human capital indicators in Malaysia for the period of 1975-2011. The bound testing approach developed within the autoregressive distribution lag (ARDL) framework is employed. The empirical results show that there is a cointegrating relationship between economic growth and the explanatory variables i.e. investment, social services expenditure and human capital indicators. The results revealed that government expenditure in social services are important to human capital development and economic growth, and an increase in health and education capital can help generate better human capital and attain economic sustainability.